2001
DOI: 10.1034/j.1399-3011.2001.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics of peptides and peptidomimetics: II. Hydroxyethylamine bioisostere‐containing peptidomimetics as substrates for the oligopeptide transporter and P‐glycoprotein in the intestinal mucosa

Abstract: Peptide bond bioisosteres, such as hydroxyethylamine (Hea), have frequently been used to stabilize metabolically labile peptide bonds in peptidomimetic drug design in an effort to increase the oral bioavailability of drug candidates. However, the impact of the peptide bond bioisosteres on the cell permeation characteristics of peptidomimetics is not well understood, particularly with respect to the effects on the substrate activity for proteins that can restrict (e.g. P-glycoprotein, P-gp) or facilitate (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Despite significant progress in understanding the molecular and cellular effects of HEAs has been done [9,[12][13][14], a few theoretical studies, to the best of our knowledge, have been reported [15][16][17][18]. More particularly, such an approach is expected to shed some light onto the role of protein-ligand interactions for this system.…”
Section: Introductionmentioning
confidence: 90%
“…Despite significant progress in understanding the molecular and cellular effects of HEAs has been done [9,[12][13][14], a few theoretical studies, to the best of our knowledge, have been reported [15][16][17][18]. More particularly, such an approach is expected to shed some light onto the role of protein-ligand interactions for this system.…”
Section: Introductionmentioning
confidence: 90%
“…The model biological model systems used in these studies included cell culture models and in situ perfusion models of the intestinal mucosa and the BBB (see the Practical Models for Biological Barriers to Drug Delivery section). The physicochemical and biological properties studied by Ron's group over about a 10 year period included the following: (i) the effect of beta-turn structures on passive diffusion of peptides and peptidomimetics through the intestinal mucosa and the BBB; [178][179][180] (ii) the effect of hydrogen bonding potential on passive diffusion and passive diffusion modified by efflux transporters of peptides and peptidomimetics through the intestinal mucosa and the BBB; [181][182][183][184][185][186] (iii) the effect of structural features of peptides and peptidomimetics on substrate activity for the peptide transporter in the intestinal mucosa; [187][188][189][190][191] and (iv) the effect of structural features, particularly size and charge, of peptides and peptidomimetics on their permeation via the paracellular route across the intestinal mucosa. 192 The results of these studies are described in several review articles.…”
Section: Characterization Of Drug-like Propertiesmentioning
confidence: 99%
“…A single chain variable fragment iBSEC1 scFv from a human-based scFv yeast display library was isolated, selectively recognizing the BACE-1 cleavage site on APP, and inhibiting BACE-1 activity and APP but not soluble Ab (Boddapati et al, 2011). Inhibition of BACE1 has been shown to induce hypomyelination, cognitive deficits, and schizophrenia-like behavior in mice and could potentially lead to epileptic seizures (Gao et al, 2001). Many macrocyclic peptidic BACE-1 inhibitors show poor blood brain barrier (BBB) permeation and high efflux (Machauer et al, 2009).…”
Section: Bace 1 Inhibitorsmentioning
confidence: 99%